2022
DOI: 10.1590/1519-6984.238110
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of scorpionic accidents in a municipality in Brazil’s northeastern

Abstract: Scorpionic accidents are a major public health problem due to the high occurrence with potential seriousness. In this manner, the research aimed to analyze the occurrence of scorpionic accidents in a municipality in the northeastern of Brazil. An exploratory, descriptive study was made, with a quantitative approach, using secondary data which was gotten from the Notifiable Diseases Information System (SINAN), from 2008 to 2018. Data such as neighborhood, presence of street markets were also used, and the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…In this study, most cases took 31-60 min from the time of envenoming until the victim had medical assistance (48.2%), with the shortest time being up to 30 min (27.7%). These results are similar to those observed in other studies, which showed that most victims had specialized assistance in less than 1 h after the sting 10,14,15 . Lisboa observed a higher incidence in the time elapsed before care from 1 to 3 h after envenomation (39.3%) 13 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, most cases took 31-60 min from the time of envenoming until the victim had medical assistance (48.2%), with the shortest time being up to 30 min (27.7%). These results are similar to those observed in other studies, which showed that most victims had specialized assistance in less than 1 h after the sting 10,14,15 . Lisboa observed a higher incidence in the time elapsed before care from 1 to 3 h after envenomation (39.3%) 13 .…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also reported a higher incidence of mild cases in several regions of Brazil, while severe cases varied from 0.4% to 13.5% [10][11][12][13] . Envenoming with T. serrulatus registered in Santa Catarina did not evolve severely, which can be associated with the lower number of cases with children in this state, since other states show a higher prevalence in children aged 0-12 years old [10][11][12][13][14][15][16] and T. serrulatus is involved in most severe cases and fatal outcomes, especially when the victims are children 17 . This was also observed in other studies, which reported a greater volume of envenomation classified as serious among children aged 4-8 years and the occurrence of one pediatric death, which evolved in less than 24 h to acute pulmonary edema and cardiogenic shock 14 .…”
Section: Discussionmentioning
confidence: 81%
“…Lisboa et al 20 sugerem que este fenômeno ocorra devido à estabilidade dessas condições climáticas, resultando na proliferação dos escorpiões durante todo o ano. Entretanto, o estudo de Santos et al 40 não observou relação significativa entre fatores climáticos e escorpionismo, mas verificou que fatores antrópicos podem potencializar a ocorrência dos acidentes.…”
Section: Discussionunclassified
“…O escorpionismo é uma condição negligenciada de áreas tropicais e subtropicais, associada às condições de desequilíbrio ambiental, pobreza, desinformação e acesso reduzido a antivenenos efetivos 40,41 . A vulnerabilidade de um indivíduo ou população relaciona-se diretamente com a susceptibilidade a determinado agravo, associada à menor disponibilidade de recursos na atenção de forma individual ou coletiva 42 .…”
Section: Discussionunclassified
“…Scorpionism in Brazil has increased significantly in the last decade, leading the ranking of accidents caused by venomous animals in the country . The evolutionary process allowed a wide adaptation of several scorpion species, such as T. serrulatus, allowing greater dissemination that led them to occupy regions ranging from deserts to urbanized centers (Dabo et al, 2011;Santos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%